What is the Actual Effect of Islamic Finance Development on the Environment? A Meta-Analysis - Hapid Durohman; Nadya Setyawati; Faatih Rahmah (Ekonomi Islam Indonesia, 2025)
Over the last three decades, Islamic finance has overgrown in global financial markets. However, several previous studies have found that economic improvement and rapid growth of the financial sector will negatively impact environmental quality. The impact of Islamic finance on the environment based on the existing literature shows varying results. Even though much research discusses the influence of Islamic finance developments on the environment, existing studies still need to be developed to obtain relevant policy recommendations. Therefore, this research was done to analyze the relationship between the development of Islamic finance and environmental aspects from various previous studies. This study uses the meta-analysis method, a statistical approach to combine evidence from different studies (heterogeneity) quantitatively. This study uses data derived from 9 previous studies. To get a depth view of the studies from multiple databases used as observations in this research. Based on the results of a meta-analysis on CO2 emissions, it can be seen that there are indications of an association between the development of Islamic finance and carbon emissions, although not significant. this study concludes that Islamic finance can reduce environmental problems, including in Indonesia. This study recommends several recommendations, including unify standards and reporting, spur innovation, and reduce barriers and costs for issuers while increasing transparency and awareness for investors of Islamic financial instruments, such as green sukuk.